Observation of the Nernst effect in a GeTe/NiFe structure - Ahn, Jeong Ung; Jeon, Jeehoon; Cho, Seong Won; Lee, OukJae; Lee, Suyoun; Koo, Hyun Cheol (Elsevier, 2023)
On the basis of second-harmonic measurements, we separated the thermal effect from the spin-orbit torque in GeTe/NiFe bilayers. The damping-like torque and thermal effect terms are phenomenologically inseparable in the second-harmonic resistance. Several thermomagnetic effects, such as the Nernst effect and spin Seebeck effect, are also mixed in the second-harmonic signals. By exploiting the different external magnetic field dependence of these terms, we extracted the noticeable thermal-related terms. In particular, the ordinary Nernst effect is dominant over other thermal effects such as the anomalous Nernst effect and the spin Seebeck effect in a GeTe/NiFe structure. Furthermore, we have investigated the dependence of the ordinary Nernst effect on the temperature and the electric field applied to GeTe channel. These findings reveal that, in a bulk Rashba device, the thermal effect must be considered when attempting to control the spin-orbit-torque-induced switching.